270 REDUCE THE RISK OF COLON CANCER WITH COLON CANCER SCREENING. (1st January 2006) - Kempe, K.
Abstract : Purpose: There are very low rates of colon cancer screening in White Sulphur Springs, Montana, population 1, 010. An educational project was designed to increase community awareness of the risk of colon cancer and the benefits from colon cancer screening. Four modalities for colon cancer screening are available: colonoscopy, barium enema, sigmoidoscopy, and fecal occult. Mountainview Medical Center is the only medical facility within a 100-mile radius. A gastroenterologist travels from Helena, MT, to perform screening exams in White Sulphur Springs on a quarterly basis, but the service is currently underutilized. Methods: A literature search using MEDLINE and UW Healthlinks was completed looking at the epidemiology of colon cancer, risk factors, and screening efficacy. In addition, insurance coverage and costs of each procedure were evaluated. Interviews were conducted with local health care providers to identify available opportunities for colon cancer screening as well as possible barriers to screening in the community. Results: Colorectal cancer ranks second to lung cancer as a cause of cancer death. Colon cancer screening, including colonoscopy, can significantly reduce the risk of colon cancer and prevent colon cancer. An article was written, including information about colon cancer risks, prevention, and costs, and was distributed to every household in the county by the local community hospital. Conclusion: Education, increased awareness of the risks of colon cancer, screening modalities, and Medicare's willingness to pay for colon cancer screening may increase dialogue between patient and practitioner regarding colon cancer as well as increase colon cancer screenings in White Sulphur Springs, Montana.